PENGARUH SYUKUR DAN LIFE SATISFACTION TERHADAP MIDLIFE CRISIS PADA WANITA DEWASA MADYA - Nabilah Aliya Mawaddah; Yulmaida Amir (Prosiding Seminar Nasional Berseri, 2020)
Middle adulthood is one of the stages of development that also has a crisis period commonly referred to as the midlife crisis. This crisis is a decline such as in terms of health, stages of leaving a career, anxiety in entering old age, and feelings of fear of death. Midlife crisis can be overcome if an individual has a sense of gratitude and life satisfaction. Gratitude and life satisfaction can help individuals to give positive evaluations and appreciate the gifts they get based on their life experiences. This study aims to determine the effect of gratitude and life satisfaction on midlife crisis in middle adult women. This research method uses quantitative research methods, where the number of participants is 182 middle-aged women who are married, and have early adult children. The scale model used is a Likert scale model. The analysis technique used in the study is multiple regression, where the results of the study indicate that there is a significant influence between gratitude towards midlife crisis with a significance value of 0,000 (P <0.01) and an insignificant relationship between life satisfaction with midlife crisis and the value of significance of 0.282 (P> 0.05) and a significant influence between gratitude and life satisfaction on midlife crisis with a significance value of 0,000 (P <0.01). R square value (R2) of 0.312 which indicates the contribution of variable gratitude and life satisfaction to midlife crisis of 31.2% with the remaining 68.8% is an unknown contribution outside this study.